Pengembangan Media Komik Digital Berbasis Budaya Bali pada Materi Gaya untuk Meningkatkan Hasil Belajar Siswa Kelas IV SD - I Wayan Dika Semara Kusuma; Luh Putu Sri Lestari; I Kadek Edi Yudiana (CV. Alim's Publishing, 2026)
This study aims to develop a Balinese culture-based digital comic learning media on the topic of force for fourth-grade elementary school students. The study also aims to determine the feasibility, practicality, and effectiveness of the media in improving students’ learning outcomes. The research method used was Research and Development (R&D) with the ADDIE model, which consists of the stages of Analyze, Design, Development, Implementation, and Evaluation. The results showed that the developed digital comic had a very high level of feasibility based on evaluations from media and material experts. The media was also considered highly practical based on teachers’ and students’ responses. In addition, the effectiveness test using the One Group Pre-test Post-test design showed a significant improvement in students’ learning outcomes after using the digital comic media. Therefore, the Balinese culture-based digital comic is considered feasible and effective as an alternative learning media for science and social studies (IPAS) on the topic of force in fourth-grade elementary school.